Difference between revisions of "009B Sample Final 1, Problem 6"
Jump to navigation
Jump to search
(Created page with "<span class="exam"> Evaluate the improper integrals: ::<span class="exam">a) <math>\int_0^{\infty} xe^{-x}~dx</math> ::<span class="exam">b) <math>\int_1^4 \frac{dx}{\sqrt{4-...") |
|||
Line 12: | Line 12: | ||
::You can write <math>\int_0^{\infty} f(x)~dx=\lim_{a\rightarrow\infty} \int_0^a f(x)~dx.</math> | ::You can write <math>\int_0^{\infty} f(x)~dx=\lim_{a\rightarrow\infty} \int_0^a f(x)~dx.</math> | ||
|- | |- | ||
− | |'''2.''' How could you write <math>\int_{-1}^1 \frac{1}{x}~dx</math> | + | |'''2.''' How could you write <math>\int_{-1}^1 \frac{1}{x}~dx?</math> |
|- | |- | ||
| | | | ||
− | ::The problem is that  <math>\frac{1}{x}</math>  is not continuous at <math style="vertical-align: 0px">x=0</math> | + | ::The problem is that  <math>\frac{1}{x}</math>  is not continuous at <math style="vertical-align: 0px">x=0.</math> |
|- | |- | ||
| | | | ||
− | ::So, you can write <math style="vertical-align: -15px">\int_{-1}^1 \frac{1}{x}~dx=\lim_{a\rightarrow 0^-} \int_{-1}^a \frac{1}{x}~dx+\lim_{a\rightarrow 0^+} \int_a^1 \frac{1}{x}~dx</math> | + | ::So, you can write <math style="vertical-align: -15px">\int_{-1}^1 \frac{1}{x}~dx=\lim_{a\rightarrow 0^-} \int_{-1}^a \frac{1}{x}~dx+\lim_{a\rightarrow 0^+} \int_a^1 \frac{1}{x}~dx.</math> |
|- | |- | ||
− | |'''3.''' How would you integrate <math style="vertical-align: -13px">\int xe^x\,dx</math> | + | |'''3.''' How would you integrate <math style="vertical-align: -13px">\int xe^x\,dx?</math> |
|- | |- | ||
| | | | ||
Line 26: | Line 26: | ||
|- | |- | ||
| | | | ||
− | ::Let <math style="vertical-align: 0px">u=x</math> and <math style="vertical-align: 0px">dv=e^xdx</math> | + | ::Let <math style="vertical-align: 0px">u=x</math> and <math style="vertical-align: 0px">dv=e^xdx.</math> |
|} | |} | ||
Line 36: | Line 36: | ||
!Step 1: | !Step 1: | ||
|- | |- | ||
− | |First, we write | + | |First, we write |
|- | |- | ||
− | |Now, we proceed using integration by parts. Let <math style="vertical-align: 0px">u=x</math> and <math style="vertical-align: 0px">dv=e^{-x}dx</math> | + | | |
+ | ::<math style="vertical-align: -14px">\int_0^{\infty} xe^{-x}~dx=\lim_{a\rightarrow \infty} \int_0^a xe^{-x}~dx.</math> | ||
+ | |- | ||
+ | |Now, we proceed using integration by parts. Let <math style="vertical-align: 0px">u=x</math> and <math style="vertical-align: 0px">dv=e^{-x}dx.</math> Then, <math style="vertical-align: 0px">du=dx</math> and <math style="vertical-align: 0px">v=-e^{-x}.</math> | ||
|- | |- | ||
|Thus, the integral becomes | |Thus, the integral becomes | ||
Line 49: | Line 52: | ||
!Step 2: | !Step 2: | ||
|- | |- | ||
− | |For the remaining integral, we need to use <math style="vertical-align: 0px">u</math>-substitution. Let <math style="vertical-align: 0px">u=-x</math> | + | |For the remaining integral, we need to use <math style="vertical-align: 0px">u</math>-substitution. Let <math style="vertical-align: 0px">u=-x.</math> Then, <math style="vertical-align: 0px">du=-dx.</math> |
|- | |- | ||
|Since the integral is a definite integral, we need to change the bounds of integration. | |Since the integral is a definite integral, we need to change the bounds of integration. | ||
|- | |- | ||
− | |Plugging in our values into the equation <math style="vertical-align: | + | |Plugging in our values into the equation <math style="vertical-align: -4px">u=-x,</math> we get <math style="vertical-align: -5px">u_1=0</math> and <math style="vertical-align: -3px">u_2=-a.</math> |
|- | |- | ||
|Thus, the integral becomes | |Thus, the integral becomes | ||
Line 100: | Line 103: | ||
!Step 1: | !Step 1: | ||
|- | |- | ||
− | |First, we write <math>\int_1^4 \frac{dx}{\sqrt{4-x}}=\lim_{a\rightarrow 4} \int_1^a\frac{dx}{\sqrt{4-x}}</math> | + | |First, we write |
+ | |- | ||
+ | | | ||
+ | ::<math>\int_1^4 \frac{dx}{\sqrt{4-x}}=\lim_{a\rightarrow 4} \int_1^a\frac{dx}{\sqrt{4-x}}.</math> | ||
|- | |- | ||
− | |Now, we proceed by <math style="vertical-align: 0px">u</math>-substitution. We let <math style="vertical-align: -1px">u=4-x</math> | + | |Now, we proceed by <math style="vertical-align: 0px">u</math>-substitution. We let <math style="vertical-align: -1px">u=4-x.</math> Then, <math style="vertical-align: 0px">du=-dx.</math> |
|- | |- | ||
|Since the integral is a definite integral, we need to change the bounds of integration. | |Since the integral is a definite integral, we need to change the bounds of integration. | ||
|- | |- | ||
− | |Plugging in our values into the equation <math style="vertical-align: - | + | |Plugging in our values into the equation <math style="vertical-align: -4px">u=4-x,</math> we get <math style="vertical-align: -5px">u_1=4-1=3</math>  and <math style="vertical-align: -3px">u_2=4-a.</math> |
|- | |- | ||
|Thus, the integral becomes | |Thus, the integral becomes |
Revision as of 12:12, 18 April 2016
Evaluate the improper integrals:
- a)
- b)
Foundations: |
---|
1. How could you write so that you can integrate? |
|
2. How could you write |
|
|
3. How would you integrate |
|
|
Solution:
(a)
Step 1: |
---|
First, we write |
|
Now, we proceed using integration by parts. Let and Then, and |
Thus, the integral becomes |
|
Step 2: |
---|
For the remaining integral, we need to use -substitution. Let Then, |
Since the integral is a definite integral, we need to change the bounds of integration. |
Plugging in our values into the equation we get and |
Thus, the integral becomes |
|
Step 3: |
---|
Now, we evaluate to get |
|
Using L'Hôpital's Rule, we get |
|
(b)
Step 1: |
---|
First, we write |
|
Now, we proceed by -substitution. We let Then, |
Since the integral is a definite integral, we need to change the bounds of integration. |
Plugging in our values into the equation we get and |
Thus, the integral becomes |
|
Step 2: |
---|
We integrate to get |
|
Final Answer: |
---|
(a) |
(b) |